First European Quality of Life Survey Methodological review - European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
This report is one of two reports written as technical assistance in preparing the second European quality of life survey (EQLS-2). While this report is a review of the first round of the EQLS in comparison to the European Social Survey (ESS), the second report provides recommendations to improve the data quality. Thereby the 'methodological review' forms the basis for the 'recommendations'. Both reports are divided into four parts: sampling, fieldwork, questionnaire and data set. This report compares the EQLS- 1 with the ESS in these four dimensions, and the 'recommendations' make specific proposals for improving quality in each of these dimensions. The methodological report is based on previous research (Kohler, 2006a, 2007). This research revealed that the key methodological weakness of EQLS-1 lay in its higher risk of sampling bias, compared to other similar surveys. In a comparison with five other social surveys, including the ESS and the Eurobarometer 62.1, the EQLS 2003 showed the highest rate of failure against so called 'internal criteria of representativeness' and the highest over-representation of women.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Social surveys -- European Union countries; Electronic books